Theme restaurants : factors affecting diners' choice intention. - Lim, William Teck Lim. (2008)
This study aims to examine the importance of the theme factor in a diner's choice of a theme restaurant in Singapore, and how other factors in a restaurant's operations are important in purchasing behaviour. These factors include price, ambience, image, location, product merchandise as well as food and service quality. A consumer survey was conducted on the patrons of three theme restaurants in Singapore and it is discovered that food quality is the key factor that affected a diner's choice.